Desenvolvimento e aplicação de indicadores da qualidade ambiental urbana: avaliação da bacia hidrográfica do Rio Barigui – Curitiba/PR - Silva, Gabriela do Vale (2016)
The rapid population growth and industrialization in urban centers, has negative impacts on water resources, mainly compromising the ability of environmental protection, with respect to quality of river basins in the cities. The basin is a complex environmental system resulting from the interrelations between society and nature, and the current situation of these areas are examples of the pressures that the environment is submitted. The use of water in the state of Paraná, is guided by the Basin Plans, while the Master Plans, seeking to order the use of land in the municipalities. These two planes overlap in dealing with water resources management. Thus, this study aims to implement an methodology Urban Environmental Quality - UEQ, making adjustments that were applied in the Bacia do rio Barigui - Curitiba / PR, to analyze the social, environmental and infrastructure interrelations. The data collected to form the UEQ database were obtained in different official institutions, which guided the adaptation of the methodology indicators. The application UEQ of the Bacia do rio Barigui, was through the basin of the division into five Environmental Units - EU, and applying UEQ indicators in each environmental unit. After the analysis of indicators and data aggregation Urban Environmental Quality Index – UEQI end was produced. All EU's assessed presented final UEQI with satisfactory quality, but the partial indexes better reflect local conditions. The results obtained by the UEQ methodology in this research was compared with the plans of the Alto Iguaçu Basin and Tributaries of the Upper Ribeira and Director of Curitiba. The UEQ method was considered appropriate to base the comparative analysis to the Basin Plan and the Master Plan. Thus, it was identified that the first consider the water quality and population density, and the second, population, housing, economic, social, security and urban mobility. The comparison between the two plans identified convergence in the use and occupation of land and water resources, but differences in aggregate format, the first use basins and sub-basins, and the second aggregation unit is the city. The results of the application of UEQ with their categories of analysis, variables and indicators in the Bacia do rio Barigui, demonstrated the potential of this methodology to make the necessary interrelations seeking an orientation managing urban watersheds.